Complication of Tracheobronchial Prosthesis: Occlusion due to Secretions - Barata, Beatriz; Urmal, Inês; Lalanda, Carlota; Salsinha Frade, Jorge; Bravo, Ana; Margarido, Elisabete (International Journal of Innovative Research in Medical Science, 2024)
A large proportion of patients with advanced lung neoplasia will develop major airway obstruction. We present a 68-year-old man with small cell lung carcinoma, with a tracheo-bronchial stent, admitted to the emergency room with sudden dyspnea, hypoxemia and abolished breath sounds on the right. The radiography showed a complete opacification of the right lung and a chest computed tomography revealed total occlusion of the stent in the right main bronchus. He underwent rigid bronchoscopy with removal of thick secretions and clots, with lung re-expansion and resolution of respiratory failure.